Wound dehiscence rates decreased in reconstructive surgery of anorectal malformations after introduction of a standardized postoperative treatment program - Tofft, Louise ; 0000-0001-5663-035X; Granéli, Christina; Hagelsteen, Kristine ; 0000-0002-6843-8995; Wester Fleur, Matilda ; 0009-0004-2606-1781; Stenström, Pernilla ; 0000-0002-5052-9944 (World Journal of Pediatric Surgery, 2025)
Background Wound dehiscence is a known complication after anorectal malformations (ARMs) surgery. The aim was to evaluate if a standardized post-posterior sagittal anorectoplasty (PSARP) treatment program decreased wound dehiscence rates. Methods Wound dehiscence rates within 30 days post-PSARP were compared in a case-control single-center study between patients with a standardized post-PSARP treatment 2017-2023, and a cohort with a non-standardized management 2001-2016. The standardized post-PSARP program comprised a minimum of 3 days of: intravenous antibiotics imipenem+cilastatin (with optional subsequent oral amoxicillin+clavulanic acid+metronidazole), fasting after primary PSARP (no stoma), urinary catheter and regular wound cleansing. Results A total of 149 patients (61% males) with various ARM subtypes were included of which 51% were reconstructed with stomas. Overall, wound dehiscence developed in 8 of 59 patients (14%) in the standardized post-PSARP program group versus 28 of 90 patients (31%) in the control group (p=0.014). In primary PSARPs (no stoma, 59% males), wound dehiscence developed in 6 of 33 patients (18%) in the standardized post-PSARP program group versus 17 of 40 patients (43%) in the control group (p=0.026). Conclusion Wound dehiscence rates may be reduced using a standardized post-PSARP treatment program.
Publisher Copyright: © Author(s) (or their employer(s)) 2025.
Keywords: Colorectal Surgery; Congenital Abnormalities; Disabled Children; Patient Outcome Assessment; Pediatrics